2021
DOI: 10.1155/2021/8388258
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Oxidative Stress in Ovarian Cancer

Abstract: Oxidative stress (OS) arises when the body is subjected to harmful endogenous or exogenous factors that overwhelm the antioxidant system. There is increasing evidence that OS is involved in a number of diseases, including ovarian cancer (OC). OC is the most lethal gynecological malignancy, and risk factors include genetic factors, age, infertility, nulliparity, microbial infections, obesity, smoking, etc. OS can promote the proliferation, metastasis, and therapy resistance of OC, while high levels of OS have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 244 publications
(308 reference statements)
0
25
0
Order By: Relevance
“…Studies have shown that when detached cancer cells are treated with platinum chemotherapy, they experience a stress state and surge of ROS formation [29]. However, the strong redox regulation ability of cancer cells ensures that cancer cells can withstand harsh conditions to survive [30]. Ferroptosis is a form of RCD caused by uncontrolled redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when detached cancer cells are treated with platinum chemotherapy, they experience a stress state and surge of ROS formation [29]. However, the strong redox regulation ability of cancer cells ensures that cancer cells can withstand harsh conditions to survive [30]. Ferroptosis is a form of RCD caused by uncontrolled redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress tolerance is a significant factor in ovarian carcinogenesis at several stages of the disease, including its onset, development, invasion, and metastasis [ 89 ]. Moreover, oxidative stress control has been considered one of the noteworthy therapeutic targets in OC.…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%
“…PCA also showed inhibition of cancer cell proliferation and apoptosis induction via reduced Bcl-2 expression, increased Bax level, activated JNK/p38 MAPK and Fas/FasL pathways, and had an inhibitory effect on genes associated with inflammation [ 84 , 87 , 88 ]. Oxidative stress control is one of the striking therapeutic targets in OC [ 89 ]. Hence, the antioxidant effect by PCA indicates its therapeutic efficacy against OC, and multiple clinical trials are already registered to evaluate its effectiveness in ovarian cancer [ 90 , 91 ].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…This condition leads to destructive biochemical processes for the cell and is one of the causes of many diseases. Currently, overproduction of ROS is associated with oncological [ 57 , 58 ], mental [ 59 , 60 ], neurodegenerative [ 61 ], and cardiovascular diseases [ 62 ], type 2 diabetes mellitus [ 63 ], chronic obstructive pulmonary disease [ 64 ], autoimmune diseases [ 65 , 66 ], the aging process [ 67 ], osteoporosis [ 68 ], asthma [ 69 ], and gastrointestinal disorders [ 70 ].…”
Section: Reactive Oxygen and Nitrogen Species (Rons) Formation And Ox...mentioning
confidence: 99%